Analisis Pengaruh Pertumbuhan Skuter Otomatis Bertenaga Listrik Terhadap Perubahan Teknologi CVT Menggunakan Model Sistem Dinamis - Yan Kurnia Hadi; Jacky Chin (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
This research shows that we all have realized the need for clean air and globally have regulated exhaust emissions from air pollution, so electric vehicles have emerged. But this phenomenon has an impact on belt companies that supply parts for CVT gasoline-powered automatic scooters because the majority of electric motors no longer need a belt as a drive transfer from the engine to the wheel. Simulated with a dynamic model for the projection of the next 20 years from 2019 to 2039, with two scenarios, namely COVID-19 and if the government's policy target of 20% of the motorbike market switches to electricity in 2025, then gradually increases to 30% in 2035. PT XYZ as a belt supplier with an 85% market share in Indonesia, will get a net profit of 50% if this scenario is achieved until 2039 became around 131 billion per year, previously with the no-scenario model it was projected to get a net profit of around 221 billion. Maybe if the demand for electric motorbikes is more than what the government has targeted, it is likely that the two-wheeled automotive belt business could be threatened in the next 15 - 20 years. Meanwhile, the largest Expense is the cost of imported materials, reaching 65% of the total cost of Expenses consisting of Salary Expenses (Salary Expense), total training costs, cost of sales, total loss costs, material costs, and Operating overhead Recommendations that business can survive, companies can reduce material costs by developing local materials, and help shape the automotive belt use ecosystem by working with automotive manufacturers.